Effectiveness and user experiences of a valgus brace in patients with knee osteoarthritis: A mixed-method randomised controlled trial - Lex D. de Jong; Babette C. van der Zwaard; Matthijs Y. H. van Blommestein; Corné J.M. van Loon (PLoS ONE, 2025)
Background Patients with medial compartment knee osteoarthritis (OA) may benefit from wearing a valgus brace, but previous studies lacked consideration for brace wearing time, co-interventions and the brace users’ perceptions. This mixed-method randomised controlled trial investigated the effectiveness of a valgus brace on knee pain and activity limitations alongside exploring user perceptions. Materials and methods Participants randomised to the intervention group (n = 23) received regular care and a customisable valgus brace for 6 months while the participants randomised to the waitlist control group (n = 23) were allowed any regular care treatment except for a knee brace. Outcomes were evaluated with a multilevel linear regression analysis at baseline, 2 weeks, 3 months and 6 months. The primary outcome was knee pain intensity at 6 months measured by a 10-cm Visual Analogue Scale (VAS). Secondary outcomes included walking distance, generic health status, knee functioning and satisfaction with the brace. Qualitative interviews were conducted with a subsample of intervention group participants and transcripts were analysed using deductive thematic analysis. Results After 6 months, only a statistically significant and clinically important difference of 2.13 cm (95% CI −3.57 to −0.69) on the VAS score for knee pain intensity after a walk test was found between the intervention and control groups. Although the qualitative findings echoed some participants’ negative or mixed feelings about the brace, several participants perceived positive changes in pain, other body functions, during activities and had positive user experiences. Conclusion Using a valgus brace decreased knee pain intensity during walking activities. Although other outcomes showed limited effectiveness, the study’s underpowered nature increased the risk of type II errors. Qualitative data highlighted positive user experiences, suggesting potential benefits beyond the measured quantitative outcomes.